Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.33549/physiolres.934017
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Concentrations and mRNA Expression of Hepatokines Fetuin A, Fetuin B and FGF21 in Physiological Pregnancy and Gestational Diabetes Mellitus

Abstract: We measured plasma concentrations, adipose tissue and placental mRNA expression of hepatokines fetuin A, fetuin B and fibroblast growth factor 21 (FGF21) in 12 healthy pregnant women (P group), 12 pregnant women with gestational diabetes (GDM) and 10 healthy non-pregnant women (N group) to explore their potential role in the etiopathogenesis of GDM. GDM and P group had comparable BMI, C-reactive protein (CRP) and glycated hemoglobin levels while IL-10 and TNF-α levels were higher in GDM group. Fetuin A and fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…We are aware of only one previous study on cord blood fetuin-A in GDM: a small study (12 GDM pregnancies, 12 controls) reported lower cord blood fetuin-A levels in GDM pregnancies 22. In contrast, our study in a large cohort (153 GDM pregnancies, 153 controls) showed similar cord blood fetuin-A concentrations between GDM and euglycemic pregnancies, suggesting that the previously reported difference might be a chance finding due to small sample size.…”
Section: Discussioncontrasting
confidence: 77%
“…We are aware of only one previous study on cord blood fetuin-A in GDM: a small study (12 GDM pregnancies, 12 controls) reported lower cord blood fetuin-A levels in GDM pregnancies 22. In contrast, our study in a large cohort (153 GDM pregnancies, 153 controls) showed similar cord blood fetuin-A concentrations between GDM and euglycemic pregnancies, suggesting that the previously reported difference might be a chance finding due to small sample size.…”
Section: Discussioncontrasting
confidence: 77%
“…Sample size calculation was done based on the previous papers by Wang et al,2017 andŠimják et al,2018; that reported the difference in FGF-21 level between diabetic patients with periodontitis and healthy controls to be 100±70 pg/mL. 14 patients were needed to detect that difference using power 95% and 5% significance level.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Iyidir et al 12 also found that fetuin-A concentration between 24th and 28th gestational weeks significantly increased in 26 women with GDM compared with 24 healthy pregnant women. However, Kralisch et al ,15 Simjak et al ,16 and Farhan et al 11 found that fetuin-A levels did not differ between women with GDM and without at 28th, 29th and 28th–38th gestational weeks, respectively. Another previous study evaluated fetuin-A levels in the first trimester (11–14 gestational weeks), and lower fetuin-A levels were found in 29 women with GDM as compared with 59 healthy pregnant women 14.…”
Section: Discussionmentioning
confidence: 97%
“…Considering GDM shared the similar pathophysiological feature of insulin resistance with T2DM, and women with GDM were at high risk of developing T2DM in later life,10 it could be speculated that fetuin-A might also be an important biomarker involved in the pathogenesis of GDM development. However, so far, limited research on the correlation between fetuin-A and GDM yielded inconsistent findings 11–16. Some of them found significant differences in fetuin-A concentration between healthy pregnant and GDM group,12–14 while others did not 11 15 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation